The Cultural and Aesthetic Significance of Motifs on Selected Asante Temples - Larbi, Stephen (2011)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Art in African Arts